Financial behavior on Investment and Financing Decision in Indonesian SME - Purwidianti, Wida; Rahmawati, Ika Yustina; Mujirahayu, Tri Septin; Fakhruddin, Iwan (Universitas Muhammadiyah Magelang, 2023)
The SME sector experienced a decline in financial performance during the pandemic. In addition, there are changes in SME owners' financial behavior, which impact financial decision-making. The financial behavior of SME owners can be seen in risk attitudes, mental accounting, and overconfidence. This study explores the relationship between risk attitudes, mental accounting, and overconfidence in investment and financing decisions. This study took the population of UKM owners in Banyumas Regency, Central Java Province, Indonesia.. The sample used in the study amounted to 116 SME owners. The results provide empirical evidence that risk attitudes and mental accounting have not significantly influenced investment decisions. Overconfidence can improve the investment decisions of SME owners. The results of the study confirm that lower-risk attitudes will have an impact on enhancing financing decisions. A high level of mental accounting will result in better financing decisions. Overconfidence does not influence financing decisions.